Theoretical investigation on the optimal PU phase relationships of regenerative cooling systems with highest efficiency. (March 2019) - Luo, Kaiqi; Hu, Jianying; Luo, Ercang; Zhang, Limin; Sun, Yanlei; Zhou, Yuan
Highlights: Systematically investigated the optimal phase relationship of regenerative coolers. The optimal phase relationship is mainly affected by cooling temperature. The pressure wave should lead for room temperature cooling, but lag for cryogenic cooling. Abstract: The phase relationship between oscillating pressure and velocity waves (PU) is one of the most crucial factors for efficient operation of regenerative coolers. However, there have been no systematic investigation on the optimal phase relationship of the regenerative coolers under different operating parameters. Thus, a theoretical investigation on their optimal phase relationship and thermodynamic performance is made in the paper. In the theoretical calculation, some main structure parameters and operating parameters were optimized for achieving highest COP with the commercial software SAGE. The simulated results mainly show that the optimal PU phase relationship is strongly affected by refrigeration temperature. Typically, the optimal inlet PU phase difference at the inlet of hot-end heat exchanger is negative for cryogenic cooling whereas the PU phase difference is positive for ambient cooling temperature. In particular, when the refrigeration temperature goes up to air-conditioning temperature range, the optimal PU phase at the inlet of hot-end exchanger can reach a very large value of about 20–30°.The above-obtained viewpoint is quite different from traditional understanding, and it is believed that our theoretical investigation will provide a valuable guideline for constructing efficient regenerative cooling systems operating in room temperature range.